Situation analysis study of street children of Khulna city, Bangladesh - Sarker, Nirmal; Islam, M. Sohedul (International Journal Of Community Medicine And Public Health, 2024)
Background: With a considerable populace of children which can be vulnerable, this observe investigated the problems skilled by way of street youngsters in Khulna city, Bangladesh. Methods: A mixed-methods approach was used in the observe, combining quantitative and qualitative techniques. One hundred and 80-8 defendants, a while six to eighteen, had been selected via practical sampling for interviews. To acquire similarly in-depth statistics, three recognition group discussions with twenty-four participants were held. This triangulation technique gave us an intensive information of the difficulties Khulna city’s street youngsters stumble upon. Results: Most street children in Khulna city were aged 10-12 years, with non-school-going boys 55.6% outnumbering school-going girls 45.5%. Financial difficulties 100% and the need to work 62.3% were the primary barriers to school attendance. A significant proportion 56% face school-related challenges, including inability to pay fees and starvation, especially among girls 61.1%. Abuse rates are high, particularly among non-school-going children, with parental and police violence being common. Support needs include financial aid for education and income-generating training, emphasizing the need for targeted interventions. Conclusions: This study confirmed that street children face significant barriers to education, with lack of support, abuse, exploitation, and poverty, reliable with prior research in Bangladesh and other developing countries.